TEACHING AT THE RIGHT LEVEL (TaRL) THROUGH THE ALL SMART CHILDREN APPROACH (SAC) IMPROVES STUDENT'S LITERATURE ABILITY - Lalu Jazuli (PROGRES PENDIDIKAN, 2022)
The TaRL approach was developed by Pratham. In his video entitled How to Teach Kids to Read in as Little as 50 Days he says: “All over the world a growing belief is that if you open a school the children will (successfully) learn. But children are not studying, for example in India 97% are enrolled in schools but 50% of children cannot read paragraphs for 2nd graders”. The stages in the implementation of SAC consist of 3 stages: assessment, grouping, and learning according to level/ability. After going through these three stages by carrying out literacy learning for 2 weeks, then a reassessment is carried out. The results of the SAC program assessment can improve children's abilities, namely at the beginner level, letters, words, and paragraphs decreased from 55% to 50%, and at the story level increased from 45% to 50%. The students who progressed to level up reached 30%. The data on increasing students' literacy skills were obtained using the Naturalistic Research method. Grade 1 to grade 6 children are assessed individually. The instrument used is a test. The tests used are letter cards, word cards, paragraph texts, and short story texts equipped with questions about the content of the story.